Surgery for encephalomalacias presenting with intractable epilepsy - P. Sarat Chandra; Abuzer Ansari; Avnish Chauhan; Amandeep Kumar; Ajay Garg; Chitra Sarkar; C.S. Bal; Manjari Tripathi (Indian Journal of Neurosurgery)
Background Surgery for intractable epilepsy caused by encephalomalacia (especially post-traumatic) has been reported very scarcely in the literature.